Serum Periostin Is Associated With Fracture Risk in Postmenopausal Women: A 7-Year Prospective Analysis of the OFELY Study - Rousseau, J. C.; Sornay-Rendu, E.; Bertholon, C.; Chapurlat, R.; Garnero, P. (The journal of clinical endocrinology and metabolism, 2014)
Purpose:Periostin (POSTN) is a secreted γ-carboxyglutamic acid-containing protein expressed mainly in the periosteum in adult individuals. POSNT deficient mice develop periodontis and osteoporosis with decreased bone strength. The relationship between serum POSTN and bone metabolism and fracture risk in postmenopausal women is unknown.Subjects and Methods:Serum POSTN was measured in 607 postmenopausal women (mean age 66.6 ± 8.4 y) from the Os des Femmes de Lyon cohort at the ninth annual follow-up visit (baseline visit of the current analysis). Nonvertebral and clinical vertebral incident fragility fractures were reported annually during 7 years. Areal bone mineral density (BMD; measured by dual energy X-ray absorptiometry) of the hip and bone markers (intact N-terminal propeptide of type I collagen, osteocalcin, and serum type I collagen C-telopeptide) were also measured.Results:At baseline, serum POSTN did not correlate with age, bone markers, and BMD. After a median of 7 years of follow-up, 75 women sustained an incident clinical vertebral or nonvertebral fragility fracture. The proportion of women who had an incident fracture was significantly higher in women with levels of POSTN in the highest quartile than that of women in the three other quartiles (19.5% vs 10.1%, P = .018) after adjustment for age and prevalent fracture. The highest quartile of POSTN was associated with an increased risk of incident fracture with a relative risk (95% confidence interval) of 1.88 (1.1–3.2) after adjustment for age, prevalent fracture, and hip BMD T-score. Patients with both low hip BMD (T-score < −2.5) and high levels of POSTN (fourth quartile) had a relative risk of fracture of 7.1 (95% confidence interval 2.4–21.8) after adjustment for age.Conclusion:High serum POSTN levels are independently associated with increased fracture risk in postmenopausal women. These data suggest that serum POSTN could be useful to improve fracture risk assessment.